Discussion on the Principles of the Canadian Charter of Rights and Freedoms - Zhang, Zhenyu (Transactions on Social Science, Education and Humanities Research, 2023)
As a country of immigration, Canada is deeply influenced by the traditional legal systems and customs of Britain and France, especially the United Kingdom. The full text of the Canadian Charter of Rights and Freedom runs through the three principles of egalitarianism, liberalism and pluralism. It is a major model in Western countries. The three principles permeate and influence each other, and do not play a completely independent role. The study of the principles of the Canadian Charter of Rights and Freedoms can help us grasp the spirit and value of its constitution from a macro perspective and pave the way for further study of its legal system.